Navigating intracranial wide-neck aneurysms: Our endovascular experience at a tertiary care centre in eastern India - Chakraborty P; Das S; Howlader S (Journal of Medical and Scientific Research)
Intracranial wide-neck aneurysms are an important subset of intracranial aneurysms and can be challenging to treat with simple endovascular coiling alone due to their broad neck. Extravascular managements of these aneurysms also pose increased risks of complications. With the advent of newer endovascular techniques such as stent assisted coiling, balloon assisted coiling, dual microcatheter coiling method, flow diverter, aneurysmal neck reconstruction devices etc, there has been a revolution in endovascular management of wide neck aneurysms. Digital subtraction angiography with 3D Digital Rotational Angiography has good spatiotemporal resolution for understanding of the pathology and confirmation of diagnosis and also provides unique possibility to perform direct endovascular embolization in the same setting and offers better outcome in terms of periprocedural duration and complications, better access of pathology, post procedural complications and duration of hospital stay compared to extravascular neurosurgical approach in spite of being costlier and less available in a health set up. In this retrospective study, we have discussed the different techniques of endovascular management of intracranial wide neck aneurysms and assessed the demographic profile, clinical presentation and endovascular management of 12 such patients presenting to our department in a 1-year period. Similar such study had not been done on Eastern Indian population before. We have shared our experience in patients presenting to a tertiary care centre of Eastern India over a 1-year period. Keywords: wide-neck aneurysms; stent-assisted coiling; balloon-assisted coiling; dual microcatheter technique; endovascular treatment